Microfinance and Loan Officers' Work Experiences: Perspectives from Zambia. Issue 9 (1st September 2016) - Siwale, Juliana
Abstract: This article studies the challenges faced by microfinance institutions in Zambia, whose remit it is to provide financial services to the poor. It focuses on loan officers – the agents of delivery on the ground. With reference to loan officers' experiences and words, the paper examines how gender and education shape and structure their day-to-day encounters. The study finds that different social spaces – 'the office' and 'the field' – and wider context explains the gendered, culturally complex and multidimensional nature of developmental work at grassroots level. Social expectations emerge as major pressure points more for female loan officers than their male counterparts, making them less suitable for microfinance work, which has traditionally targeted poor women.